so sánh \(\frac{2009^{2008}+1}{2009^{2009}+1}\)và \(\frac{2009^{2008}+5}{2009^{2008}+9}\)
SO SÁNH CÁC SỐ SAU
A=2008^2009+2/2008^2009-1 vàB=2008^2009/2008^2009-3
so sánh\(\frac{2009^{2008+1}}{2009^{2009+1}}\) và \(\frac{2009^{2008+5}}{2009^{2009+9}}\)
So sánh : \(A=\frac{2008}{2009}+\frac{2009}{2010}+\frac{2010}{2011}vàB=\frac{2008+2009+2010}{2009+2010+2011}\)
So sánh \(\frac{2008}{2009}+\frac{2009}{2010}và\frac{2008+2009}{2009+2010}\)
So sánh
(2008^2009+1)/ (2008^2009-1) và (2008^2009)/ (2008^2009-3)
So Sánh
\(\frac{2007}{2008}+\frac{2008}{2009}\)và \(\frac{2007}{2008}+\frac{2008}{2009}\)
2. So sánh A và B:
A= 2006/2007 - 2007/2008 + 2008/2009 - 2009/2010
B=-1/2006*2007 - 1/2008*2009
So sánh : A=\(\frac{2008}{2009}\)+\(\frac{2009}{2010}\)+\(\frac{2010}{2011}\)và B=\(\frac{2008+2009+2010}{2009+2010+2011}\)